Astrocytic NF‐κB brings the best and worst out of microglia. (23rd July 2018) - Dokalis, Nikolaos; Prinz, Marco
Abstract : The role of astrocytes and microglia in neurodegenerative diseases such as amyotrophic lateral sclerosis (ALS) remains incompletely understood. In this issue of The EMBO Journal, Alami et al (2018 ) employ a sophisticated genetic system that allows precise temporal control of NF‐κB activation in astrocytes to demonstrate that the timing of astrocyte activation is a key determinant of disease progression. Their results suggest that astrocyte activation drives microglia proliferation and that this can amplify not only the protective microglial effects in the presymptomatic phase of ALS, but also the detrimental microglial effects in the symptomatic phase. Abstract : Quantitative proteomics identifies an ES cell‐specific form of a chromatin repressor complex, which shapes the particular chromatin state required for proliferation and self‐renewal of these cells.